Designing System Information DAMRI (SIRI) in an Effort to Improve Damri Transportation Services User in Bandung - Guntur Ramadhan; Fauzan Sukmapratama; Hafizh Firdaus Yuspriana; Dian Anggraini (Universitas Pendidikan Indonesia (UPI), 2022)
The DAMRI bus or Djawatan Angkoetan Motor Republic Indonesia is one of the mainstays of public transportation for residents in the Bandung area with relatively low costs for the facilities with varied travel routes. The existence of this DAMRI bus is able to help increase the productivity of the community to fulfil needs. However, any of these advantages can be difficult for users of the bus service to obtain due to waiting for a bus for a long time. This is because the number of routes is not as many as other public transportation and there is a lack of information about the bus schedule for each route, so that service users can only guess the arrival time of the bus. This design is carried out by the observation method of collecting data on the experience of DAMRI bus service users through questionnaires, website-based software development methods, and literature reviews. The purpose of this design is to provide convenience to customers in accessing information on DAMRI Bus transportation through their smartphones or computers. The result of this design is a media route schedule information, routes, and costs of each route for users with a minimalist design and easy to understand is also used.